2016
DOI: 10.3923/ijcr.2016.69.81
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bone Marrow to Potentiate the Anti-Tumor Effect of Tyrosine Kinase Inhibitor in Preclinical Rat Model of Human Glioblastoma

Abstract: Antiangiogenic agents caused paradoxical increase in pro-growth and pro-angiogenic factors and caused tumor growth in glioblastoma (GBM). It is hypothesized that paradoxical increase in pro-angiogenic factors would mobilize Bone Marrow Derived Cells (BMDCs) to the treated tumor and cause refractory tumor growth. The purposes of the studies were to determine whether whole body irradiation (WBIR) or a CXCR4 antagonist (AMD3100) will potentiate the effect of vatalanib (a VEGFR2 tyrosine kinase inhibitor) and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
10
1
Order By: Relevance
“…The effect of AMD3100 in comparison to VEGF pathway inhibitors has been extensively researched in preclinical in vivo models [94,149,150]. These studies have found that AMD3100 exceeded the classical AAT regarding tumor growth rate reduction [94,[149][150][151], blood vessel density [149,151] and other vasculogenic parameters [94,150,151]. Kioi et al found that radiotherapy, one of the pillars of the GBM standard-of-care therapy, triggers the recruitment of BMDCs into the tumors [94].…”
Section: Antiangiogenic Approaches Targeting Chemokine Receptors/chemokinesmentioning
confidence: 99%
“…The effect of AMD3100 in comparison to VEGF pathway inhibitors has been extensively researched in preclinical in vivo models [94,149,150]. These studies have found that AMD3100 exceeded the classical AAT regarding tumor growth rate reduction [94,[149][150][151], blood vessel density [149,151] and other vasculogenic parameters [94,150,151]. Kioi et al found that radiotherapy, one of the pillars of the GBM standard-of-care therapy, triggers the recruitment of BMDCs into the tumors [94].…”
Section: Antiangiogenic Approaches Targeting Chemokine Receptors/chemokinesmentioning
confidence: 99%
“…BMDCs play a crucial role in the progression of angiogenesis and resistance to anti-angiogenic therapy. Many studies have shown that recruitment of BMDCs in GBM can cause resistance to vatalanib treatment and correspondingly the depletion of BMDCs can potentiate the effects of vatalanib 95 97 . Hypoxia-regulated neuropilin-1 (Nrp1), a marker of pro-angiogenic macrophages, can regulate the infiltration of TAMs into tumor hypoxic regions, and loss of Nrp1 in macrophages reduced angiogenesis and tumor growth 98 .…”
Section: The Role Of Stromal Cells In Resistance To Anti-angiogenic Tmentioning
confidence: 99%
“…In addition, our study found a significantly higher number of GFP+ bone marrow cells in close proximity to CD11b+ and F4/80+ cells [ 37 ]. In another study, we reported that the paradoxical growth of tumor following Vatalanib treatment was controlled by inhibiting the mobilization of BMDCs and disrupting the CXCR4-SDF-1α interaction using whole body irradiation and AMD3100, respectively [ 38 ]. BMDCs orchestrated the therapeutic resistance to AAT in a GBM model.…”
Section: Overarching Challengesmentioning
confidence: 99%